Women as heads of households in Germany and France: evidence from the 1846 censuses - Gehrmann, Rolf (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
Abstract: This is the first study to be based on individual census data from 1846, and it analyses the position of women as heads of households in the former German Customs Union and France. The data provide information about an important stage of gender-specific life-courses, i.e. temporary or permanent function as heads of household. A cross-sectional comparison reveals regional features, differences between urban and rural areas and the conditions favourable to the formation of female-headed households. Certain forms of stem families were more conducive than the nuclear households; the textile industry more than metal crafts, the urban environment more than the rural, and even illegitimacy was a factor. Within rural areas, a comparison with earlier periods shows a trend towards more female-headed households, whereas within towns this is less evident. Nearly all the German towns in the sample were still preindustrial, and the high rate of female-headed households was not linked to particular favourable employment facilities. The comparison with earlier periods also reveals a change in the definition of an independent household. Contrastingly, the legal framework had no great influence on this cross-sectional study. Key words: Census, households, women (gender), Germany, France, 19th century Resumen: El presente trabajo es el primero en basarse en datos individuales de censos de 1846, y estudia la posición de mujeres cabeza de hogar en Francia y la antigua Unión aduanera alemana. Los datos presentan información sobre una etapa importante del ciclo de vida en función del género, es decir la función, temporal o permanente, de jefes de familia. Una comparación transversal pone de manifiesto las características regionales, las diferencias entre áreas urbanas y rurales, y las condiciones favorables a la creación de hogares encabezados por mujeres. Algunos tipos de familias troncales eran más propicios que los hogares nucleares; la industria textil más que la metalúrgica, el ambiente urbano más que el rural, e incluso la ilegitimidad era un factor determinante. En las áreas rurales, la comparación con periodos anteriores muestra una tendencia al aumento de hogares con jefatura femenina, mientras que en los pueblos esta es menos evidente. La casi totalidad de los pueblos alemanes estudiados aún eran preindustriales, y no se encontró una relación entre la tasa elevada de hogares encabezados por mujeres y las oportunidades de empleo particularmente favorables. La comparación con periodos anteriores también demuestra un cambio en la definición del hogar independiente. Por el contrario, el marco jurídico no presenta una influencia considerable en este estudio transversal. Palabras clave: Censo, hogares, mujeres (género), Alemania, Francia, siglo XIX doi: https://doi.org/10.20318/revhisto.2017.3704